Therapeutic strategies and nano-drug delivery applications in management of ageing Alzheimer's disease - Govindarajan Karthivashan; Palanivel Ganesan; Shin-Young Park; Joon-Soo Kim; Dong-Kug Choi (Taylor & Francis Group, 2018)
In recent years, the incidental rate of neurodegenerative disorders has increased proportionately with the aging population. Alzheimer's disease (AD) is one of the most commonly reported neurodegenerative disorders, and it is estimated to increase by roughly 30% among the aged population. In spite of screening numerous drug candidates against various molecular targets of AD, only a few candidates - such as acetylcholinesterase inhibitors are currently utilized as an effective clinical therapy. However, targeted drug delivery of these drugs to the central nervous system (CNS) exhibits several limitations including meager solubility, low bioavailability, and reduced efficiency due to the impediments of the blood-brain barrier (BBB). Current advances in nanotechnology present opportunities to overcome such limitations in delivering active drug candidates. Nanodrug delivery systems are promising in targeting several therapeutic moieties by easing the penetration of drug molecules across the CNS and improving their bioavailability. Recently, a wide range of nano-carriers, such as polymers, emulsions, lipo-carriers, solid lipid carriers, carbon nanotubes, metal based carriers etc., have been adapted to develop successful therapeutics with sustained release and improved efficacy. Here, we discuss few recently updated nano-drug delivery applications that have been adapted in the field of AD therapeutics, and future prospects on potential molecular targets for nano-drug delivery systems.